2021
DOI: 10.24854/jpu189
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the life satisfaction of Indonesian Christian employees: Examining the role of religiosity, perceived organizational support, and meaningful work

Abstract: Life satisfaction plays important role in employees’ work performance and is related to the internal factors of religiosity, perceived organizational support, and meaningful work. This research aims to investigate the influence of religiosity and perceived organizational support on life satisfaction through meaningful work as a mediator for 263 respondents from 118 organizations in Indonesia. This research found that a significant number of participants (71.86%) were satisfied with their life. The findings sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
7
0
28

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 26 publications
4
7
0
28
Order By: Relevance
“…These results are consistent with research by Novanto, et al (2021) which also did not find any effect of social support on the life satisfaction of 263 Christian employees in Indonesia. They differ, however, with Kasprzak (2010), who found a relationship between social support and life satisfaction in Poland.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…These results are consistent with research by Novanto, et al (2021) which also did not find any effect of social support on the life satisfaction of 263 Christian employees in Indonesia. They differ, however, with Kasprzak (2010), who found a relationship between social support and life satisfaction in Poland.…”
supporting
confidence: 92%
“…In the context of this research, it can be concluded that seminary lecturers with high religiosity will feel that the tasks they do are important and beneficial for many people, which can affect how they make their meaning of work. The results of this study also supported previous research by Novanto, et al (2021) which also found the influence of religiosity on the meaning of work in 263 Christian employees in Indonesia.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The main purpose of this study was to explore the link between religiosity and meaningful work and to investigate the mediating roles of existential labor (surface acting and deep acting) among Malaysian Muslim employees. Despite its prevalence and importance in value systems, limited studies have empirically examined the association between religiosity and meaningful work [ 7 ] or meaning-making [ 6 ]. Thus, this study integrated COR theory [ 12 ] and the concept of self-concept–job fit [ 13 ] to examine whether different religiosity types (i.e., IR and ER) yielded dissimilar impacts on employees’ following existential labor strategies and meaningful work.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indeed shown a positive relationship between religiosity and work variables, for example, in terms of organizational commitment, job satisfaction, organizational citizenship behavior, and employee performance [ 2 6 ]. However, limited studies have investigated the impact of religiosity on meaningful work, broadly defined as work that is personally significant and worthwhile [ 6 , 7 ]. The relevance of religiosity in terms of meaningful work is worthy of further study as meaningful work is known to foster several critical work outcomes, namely, job satisfaction (e.g., [ 8 ]), work engagement (e.g., [ 9 ]), and employee retention (e.g., [ 10 ]).…”
Section: Introductionmentioning
confidence: 99%